2011
DOI: 10.1007/s11764-011-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and follow-up of adolescent and young adult cancer survivors: the AYA HOPE Study

Abstract: IntroductionCancer is rare in adolescents and young adults (AYA), but these patients have seen little improvement in survival in contrast to most other age groups. Furthermore, participation in research by AYAs is typically low. We conducted a study to examine the feasibility of recruiting a population-based sample of AYA survivors to examine issues of treatment and health outcomes.MethodsIndividuals diagnosed in 2007–08 and age 15–39 at the time of diagnosis with acute lymphocytic leukemia, Hodgkin lymphoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
164
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(182 citation statements)
references
References 14 publications
16
164
1
1
Order By: Relevance
“…The high enrollment rate of YAs who were in early treatment confirms their willingness to participate in PA studies, which is consistent with earlier studies indicating that YA survivors are interested in learning about PA. 18,19 The study completion rate of 71% is within range of PA studies with older adult cancer patients during treatment 3 and somewhat lower than other longitudinal studies with YA survivors of AYA cancers. [19][20][21] As a measure of functional capacity, the 6MWT was easy and safe for the YAs to complete. Their walk distances showed a wide range of exercise capacity-as low as 50% and as high as 90%-when compared to healthy persons of comparable age, gender, height, and weight.…”
Section: Discussionmentioning
confidence: 99%
“…The high enrollment rate of YAs who were in early treatment confirms their willingness to participate in PA studies, which is consistent with earlier studies indicating that YA survivors are interested in learning about PA. 18,19 The study completion rate of 71% is within range of PA studies with older adult cancer patients during treatment 3 and somewhat lower than other longitudinal studies with YA survivors of AYA cancers. [19][20][21] As a measure of functional capacity, the 6MWT was easy and safe for the YAs to complete. Their walk distances showed a wide range of exercise capacity-as low as 50% and as high as 90%-when compared to healthy persons of comparable age, gender, height, and weight.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, several psychosocial factors playing a role in clinical trial enrollment may also increase or decrease adherence to clinical trials among adolescents. 54 Some of the factors may include: (1) openness and frequency of communication between the adolescent, parents, and providers; (2) the adolescent' s role in making decisions at different aspects of treatment; (3) the adolescent' s knowledge of treatment and treatment-related adverse effects; and (4) 64 In addition to future research needs, there are several practice-based and applied considerations that can be implemented to improve enrollment and adherence among adolescents. Recognizing and respecting the need for autonomy versus dependency in adolescent medical decision-making is important for both parents and providers.…”
Section: Psychosocial Barriers and Facilitators Affecting Adherence Tmentioning
confidence: 99%
“…2,5,11,12 The AYA Health Outcomes and Patient Experience (HOPE) Study, which has followed 524 AYA patients, reported that only 7% of respondents had participated in a clinical trial. 13 2 Figure 1 illustrates that overall survival trends are improving for malignant cancers among all age groups in AYAs. However, for certain cancer types, this is not the case.…”
Section: Resultsmentioning
confidence: 99%
“…The AYA HOPE Study revealed the most common reason that AYAs did not participate in clinical trials was the fear that the medications that would be given to them were not sufficiently tested. 13 Certainly, explaining what is known about the medication being studied including potential side effects may help alleviate these fears and lead to improved enrollment. More importantly, providers should demystify the concept of clinical trials with patients, and convey that these trials are our "gold standard" of research in medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation